A negative photosensitive polyimide resin glue with high resolution and a preparation method and use thereof

CN122923358APending Publication Date: 2026-10-16BEIJING KEGUANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611001454.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

与正性PSPI相比,负性PSPI的光刻分辨率较低

Benefits of technology

[0041]The high-resolution negative PSPI resin solution described in this invention exhibits excellent storage stability and photolithography processability. It can form a uniformly thick liquid film on the surface of a 12-inch silicon wafer using spin-coating, or on a large-area (≥600mm x 600mm) glass substrate using inkjet printing. The resulting resin 3D pattern, after photolithography processes such as pre-baking, exposure, and development, features high resolution and controllable steepness. The resin film formed after low-temperature curing (≤230℃) possesses excellent comprehensive mechanical properties, resistance to damp heat, chemical corrosion resistance, and copper adhesion. Furthermore, the multilayer metal interconnect (RDLs) structure fabricated from the negative PSPI resin solution exhibits low internal stress, significantly reducing the warpage of the reconstructed wafer and preventing interlayer cracking in the RDL structure. It is suitable for fabricating RDLs on silicon wafer surfaces and large-area glass substrate surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122923358A_ABST
    Figure CN122923358A_ABST
Patent Text Reader

Abstract

The application discloses a negative photosensitive polyimide resin glue liquid with high resolution and a preparation method and application thereof. The prepared negative PSPI resin glue liquid has excellent photoetching process, and can be coated on the surface of a silicon wafer through rotation, and can form a liquid glue film with uniform thickness on the surface of a large-area glass substrate through film forming processes such as inkjet printing and curtain coating. After pre-baking, exposure, development, rinsing and heating and curing, the liquid glue film can form a high-quality three-dimensional stereolithography pattern with high photoetching resolution. The cured resin of the photoetched pattern has excellent comprehensive mechanical properties, moisture resistance, chemical immersion resistance and copper surface adhesion. Meanwhile, the multilayer metal interconnection circuit (RDLs) structure prepared from the negative PSPI resin glue liquid has low internal stress, can obviously reduce the warping deformation degree of a reconstituted wafer, avoids interlayer cracking of the RDLs structure, and is suitable for manufacturing a multilayer metal interconnection structure on the surface of a silicon wafer and the surface of a large-area glass substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-resolution negative photosensitive polyimide resin liquid, its preparation method and uses, belonging to the field of materials preparation technology. Background Technology

[0002] In recent years, with the rapid development of high-density integrated circuit wafer-level packaging and panel-level packaging technologies, higher requirements have been placed on the comprehensive performance of photosensitive interlayer dielectric materials, including photosensitive polyimide resin (PSPI) and photosensitive polybenzoxazole resin, including better photolithography processability, lower curing temperature, and higher heat resistance and mechanical properties.

[0003] Photosensitive photosensitive polymeric materials (PSPIs) are broadly classified into positive and negative PSPIs. Compared to positive PSPIs, negative PSPIs have lower photolithographic resolution. For a PSPI film with a pre-baked thickness of 8.0 μm, after exposure, development, and rinsing, the aperture resolution of positive PSPIs can reach 5.0 μm, while that of negative PSPIs is limited to 8.0 μm. Therefore, improving the photolithographic resolution of negative PSPIs has been a focus of research.

[0004] To address the low photolithographic resolution of negative photosensitive polyimide resins, this invention introduces highly transparent flexible aliphatic segments into the main chain structure of photocrosslinked polyaminate resins. These flexible aliphatic segments impart high transmittance or low absorption to the polyaminate resin, improving the transmission efficiency of ultraviolet light along the thickness direction of the resin film during exposure and reducing light scattering in the planar direction, thus effectively improving the photolithographic resolution of negative polyimide resins. Furthermore, introducing flexible aliphatic segments into the polyaminate main chain structure effectively reduces the modulus of the cured resin film, minimizing shrinkage stress and warpage during high-temperature curing. Summary of the Invention

[0005] In view of the above shortcomings, this invention discloses a high-resolution photosensitive polyimide resin solution, its preparation method, and its applications. The prepared negative PSPI resin solution has excellent photolithography processability. It can be spin-coated onto the surface of 6-12 inch silicon wafers, and can also form a uniformly thick liquid film on the surface of large-area glass substrates (≥600mm x 600mm) through inkjet printing, curtain coating, and other film-forming processes. After pre-baking, exposure, development, rinsing, and heat curing, the liquid film can form a high-quality three-dimensional photolithography pattern with high aperture resolution. The cured resin of the formed photolithography pattern has excellent comprehensive mechanical properties, resistance to damp heat, resistance to chemical corrosion, and copper adhesion. At the same time, the multilayer metal interconnect (RDL) structure made by the negative PSPI resin solution has low internal stress, which can significantly reduce the warpage of the reconstructed wafer and avoid interlayer cracking of the RDL structure. It is suitable for fabricating multilayer metal interconnect (RDL) structures on the surface of silicon wafers and large-area glass substrates.

[0006] To achieve the above-mentioned technical effects, the present invention employs the following technical means:

[0007] This invention first discloses a high-resolution negative photosensitive polyimide resin adhesive, comprising:

[0008] The composition includes 100 parts of photocrosslinkable polyamide ester resin, 50-150 parts of solvent, 0.01-20 parts of photocurable crosslinking agent, 0.01-10 parts of photocurable initiator, 0.01-10 parts of photosensitizing accelerator, 0.01-10 parts of thermal crosslinking agent, 0.01-10 parts of low-temperature curing accelerator, 0.01-10 parts of polymerization inhibitor, 0.01-10 parts of copper discoloration inhibitor, 0.01-10 parts of tackifier, and 0.01-10 parts of toughening agent; wherein:

[0009] The main chain structure of the photocrosslinkable polyamic acid ester resin contains highly transparent aliphatic segments and methacrylate groups that can undergo photocrosslinking reactions after being irradiated with ultraviolet light.

[0010] Furthermore, the photocrosslinkable polyamic acid ester resin is prepared by the following method:

[0011] (1) Aromatic tetracarboxylic dianhydride and hydroxyl-containing (meth)acrylate are dissolved in an organic solvent and esterified under heating to form an aromatic diester dianhydride solution;

[0012] (2) The aromatic diester diacid solution is reacted with thionyl chloride to form the corresponding aromatic diester diacyl chloride solution;

[0013] (3) Under cooling conditions, the aromatic diamine solid is added in portions to the above aromatic diester diacyl chloride solution and stirred at room temperature to 40°C for 0.1 to 10 h; then, a reactive end-capping agent is added and the reaction is continued to be stirred to form a photocrosslinked polyamic acid ester resin solution.

[0014] Further, the aromatic tetracarboxylic dianhydride includes two types: aromatic tetracarboxylic dianhydride-1 and aromatic tetracarboxylic dianhydride-2. Aromatic tetracarboxylic dianhydride-1 includes at least one of 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride, 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyldodecane dianhydride, and bis(triphenylamine)-bisphenol A ester. Aromatic tetracarboxylic dianhydride-2 includes at least one of pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, and 2,2-bis(4-benzenetetracarboxylic anhydride)hexafluoropropane, and a mixture thereof in any proportion.

[0015] The weight ratio of aromatic tetracarboxylic dianhydride-1 to aromatic tetracarboxylic dianhydride-2 is 1~100:100.

[0016] Further, the hydroxyl-containing (meth)acrylate includes at least one of 2-methacryloyloxyethanol, 2-hydroxy-3-methoxypropyl methacrylate, and 2-hydroxy-3-butoxypropyl methacrylate, and a mixture thereof in any proportion;

[0017] The organic solvent is selected from at least one of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, and tetrahydrofuran;

[0018] The aromatic diamine includes at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)-benzene, and 2,2-bis[4-(4-aminophenoxy)phenyl)]propane, and mixtures thereof in any proportion.

[0019] The reactive capping agent includes at least one of phthalic anhydride, 3-methylphthalic anhydride, acetic anhydride, aniline, and methylamine.

[0020] Further, the photocurable crosslinking agent includes at least one of diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and propylene glycol dimethacrylate, and the mass ratio of the agent to the photocrosslinkable polyamic acid ester resin is 0.1~10:100;

[0021] The photocuring initiator includes at least one of benzophenone, 1-hydroxycyclohexylphenyl ketone, 2-methylthioxanone, and benzoyldimethyl ketal;

[0022] The photosensitizer includes at least one of 4-morpholinobenzophenone and 4,4'-bis(diethylamino)benzophenone; the thermal crosslinking agent includes at least one of 2,6-dimethoxymethyl-4-tert-butylphenol and 2,6-dimethoxymethyl-p-cresol.

[0023] The low-temperature curing accelerator includes at least one of bis(triethanolamine) diisopropoxide titanium and tetra(n-butanol) titanium;

[0024] The polymerization inhibitor includes at least one of hydroquinone, N-nitrosodiphenylamine, and p-tert-butylcatechol; the copper color-changing inhibitor includes at least one of toluenetriazole, 5-methyl-1H-benzotriazole, and 2,6-di-tert-butyl-4-methylphenol.

[0025] The adhesive aid includes at least one of γ-aminopropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane;

[0026] The toughening agent refers to a thermoplastic polymer resin containing reactive functional groups with a weight average molecular weight of less than 100,000, including at least one of thermoplastic polyimide resin, silicone-modified polyimide resin, and polymethacrylate resin.

[0027] The present invention also discloses a method for preparing a negative photosensitive polyimide resin liquid according to any of the above-mentioned methods, comprising:

[0028] (1) Aromatic tetracarboxylic dianhydride and hydroxyl-containing (meth)acrylate are dissolved in an organic solvent and esterified under heating to form an aromatic diester dianhydride solution;

[0029] (2) The aromatic diester diacid solution is reacted with thionyl chloride to form an aromatic diester diacid chloride solution;

[0030] (3) Under cooling conditions, the solid aromatic diamine is added in portions to the solution of aromatic diester diacyl chloride, and the mixture is stirred at room temperature to 40°C for 0.1 to 10 hours. A reactive end-capping agent is added to continue the reaction to form a photocrosslinked polyamic acid ester resin solution.

[0031] (4) Mix the photocrosslinked polyamic acid ester resin with the solvent, and stir and dissolve it under yellow light and nitrogen protection to form a homogeneous solution;

[0032] (5) Add photocurable crosslinking agent, photocurable initiator, photosensitive accelerator, thermal crosslinking agent, low temperature curing accelerator, polymerization inhibitor, copper discoloration inhibitor, adhesion promoter and toughening agent to the homogeneous solution in step (4), and stir until completely dissolved to form a homogeneous solution;

[0033] (6) Adjust the solid content and viscosity of the homogeneous solution obtained in step (5), filter, and obtain negative PSPI resin solution.

[0034] Further, in step (1), the molar ratio of the aromatic tetracarboxylic dianhydride to the hydroxyl (meth)acrylate is 1:1.5~2.0, the esterification reaction temperature is 20~150℃, and the reaction time is 0.5~96h;

[0035] The molar ratio of the aromatic diester diacid to thionyl chloride in step (2) is 1:1.5~3, the reaction temperature is -30~50℃, and the reaction time is 1~48h;

[0036] In step (3), the molar ratio of aromatic diester diacyl chloride to aromatic diamine is 1:0.8~1.2, the reaction temperature is -30~10℃, and the reaction time is 0.5~96h.

[0037] Furthermore, when the solid content of the negative PSPI resin solution in step (6) is 10-45 wt.%, the solution viscosity at room temperature is 100-5500 mPa·s, and the solution viscosity change rate is less than 10% after being placed at room temperature for 7 days.

[0038] The present invention also discloses a negative PSPI resin solution prepared according to any of the above preparation methods.

[0039] The present invention also discloses the application of any of the above-mentioned negative PSPI resin solutions in the preparation of multilayer interlayer insulating and passivation protective layers on silicon wafers and large-area glass substrates.

[0040] The beneficial effects of this invention are as follows:

[0041] The high-resolution negative PSPI resin solution described in this invention exhibits excellent storage stability and photolithography processability. It can form a uniformly thick liquid film on the surface of a 12-inch silicon wafer using spin-coating, or on a large-area (≥600mm x 600mm) glass substrate using inkjet printing. The resulting resin 3D pattern, after photolithography processes such as pre-baking, exposure, and development, features high resolution and controllable steepness. The resin film formed after low-temperature curing (≤230℃) possesses excellent comprehensive mechanical properties, resistance to damp heat, chemical corrosion resistance, and copper adhesion. Furthermore, the multilayer metal interconnect (RDLs) structure fabricated from the negative PSPI resin solution exhibits low internal stress, significantly reducing the warpage of the reconstructed wafer and preventing interlayer cracking in the RDL structure. It is suitable for fabricating RDLs on silicon wafer surfaces and large-area glass substrate surfaces. Attached Figure Description

[0042] Figure 1 This is a chemical structure diagram of a photocrosslinked polyamide ester resin. Detailed Implementation

[0043] The present invention will be further described in detail below with reference to embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0044] Comprehensive performance evaluation method:

[0045] The preparation method of the negative photosensitive polyimide precursor resin solution is described in detail below through examples; the performance of the negative PSPI resin solution is evaluated using the following evaluation methods:

[0046] 1) Photolithography process: Negative PSPI resin liquid is applied to the surface of a glass substrate by inkjet printing to form a liquid film of uniform thickness (12.0-12.5 μm); after baking at 100-125℃ for 1-3 min, a mask is placed and exposed with ultraviolet lamps (i and g lines); spray development is performed using cyclopentanone developer, and after rinsing with propylene glycol methyl ether acetate, it is cured in a nitrogen-protected oven (150℃ / 1h, 200℃ / 1h, 230℃ / 1h) to obtain a cured resin stereolithographic pattern (8.0 μm), and its aperture resolution and steepness are observed.

[0047] 2) Mechanical properties of the film: The adhesive solution is sprayed onto the surface of the glass substrate to form an adhesive film; after baking at 120℃ for 3 min, it is exposed to ultraviolet light; after development and rinsing, it is cured by heating (150℃ / 1h, 200℃ / 1h, 230℃ / 1h). The silicon wafer with the film is immersed in 47% HF for 5-10 min to peel off the polyimide film and perform tensile tests.

[0048] 3) Adhesion to copper surface: The adhesive was inkjet printed onto the surface of a glass substrate to form an adhesive film; after baking, exposure, development, rinsing, and heating curing (150℃ / 1h, 200℃ / 1h, 230℃ / 1h), a polyimide film with a thickness of 8.0 μm was obtained. The adhesion between the polyimide film and the copper surface was determined using the cross-cut adhesion test according to the ASTM D3359 standard method.

[0049] 4) Chemical resistance: The cured polyimide photolithographic pattern was immersed in a caustic solution (1 wt.% potassium hydroxide + 39 wt.% 3-methoxy-3-methyl-1-butanol + 60 wt.% DMSO) at 100°C for 1 hour, then washed with water and air-dried. The chemical resistance was evaluated by measuring the change in film thickness and observing under an optical microscope.

[0050] 5) Moisture and heat resistance: The adhesive is sprayed onto a large-area glass substrate with copper-tin protrusions of 15 μm height to form a liquid adhesive film; after baking, exposure, development, rinsing and heating curing (150℃ / 1h, 200℃ / 1h, 230℃ / 1h), a cured polyimide layer film is formed on the substrate surface; the substrate is placed in a constant temperature and humidity chamber at 120℃ / 100% RH for 500 hours of moisture and heat resistance test.

[0051] 6) Residual internal stress: A liquid adhesive film is formed on the surface of a silicon wafer using a spin coating process; after baking, exposure, development, rinsing, and heating curing (150℃ / 1h, 200℃ / 1h, 230℃ / 1h), a polyimide film with a thickness of 10 μm is formed. The residual internal stress is measured using a film internal stress testing device.

[0052] 7) Overall performance: If all indicators are "Excellent", the overall performance evaluation is "Excellent"; if one indicator is "Good", the overall performance evaluation is "Good"; if one indicator is "Poor", the overall performance evaluation is "Poor".

[0053] Polyamate ester (PAE) resin synthesis:

[0054] Resin Synthesis Examples 1-15

[0055] Resin Synthesis Example 1

[0056] In a 500 ml three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA), Mw = 332.21, 187-188 °C), 26.03 g (0.20 mol.) 2-hydroxyethyl methacrylate (HEMA), 15.82 g (0.20 mol.) pyridine, and 129 g N-methylpyrrolidone (NMP) were added. The mixture was stirred at room temperature for 6 h to produce the corresponding aromatic diacid dimethacrylate. The product was then reacted with 23.79 g SOCl2 at 0-10 °C for 2 h, followed by a reaction at room temperature for 4 h to produce a solution of the corresponding BCDA diacyl chloride dimethacrylate.

[0057] In a 1L three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, 20.02g (0.1 mol.) of 4,4'-diaminodiphenyl ether (44ODA) and 158g of NMP were added and stirred until dissolved to form a homogeneous transparent solution (44ODA / NMP). The BCDA dichlorodimethyl acrylate solution prepared above was added dropwise to the 44ODA / NMP solution over a period of 0.5h. The reaction was then allowed to proceed at room temperature for 10h. Then, 1.48g (0.010 mol.) of phthalic anhydride was added, and stirring was continued for 1h. The reaction solution was poured into 5L of deionized water, the solid precipitated, filtered, and vacuum dried to obtain primary polyamic acid ester resin (PAE-1-1). This solution was then dissolved in tetrahydrofuran to form a solution. Residual metal or non-metal ions were removed by adsorption with anionic and cationic resins to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-1: BCDA-44ODA).

[0058] Resin Synthesis Example 2

[0059] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 48.63 g (0.10 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-2: BODA-44ODA).

[0060] Resin Synthesis Example 3

[0061] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 59.84 g (0.10 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyldodecane dianhydride (BDDA, Mw = 598.41, 121-126 °C) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-3: BDDA-44ODA).

[0062] Resin Synthesis Example 4

[0063] In resin synthesis example 1, 33.22 g (0.10 mol.) of 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 57.64 g (0.10 mol.) of bis(trimellitate) dianhydride (IPDA, Mw = 576.36, mp 192-193 °C) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-4: IPDA-44ODA).

[0064] Resin Synthesis Example 5

[0065] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by a mixture of 24.31 g (0.05 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) and 15.53 g (0.05 mol.) 3,3,4',4'-diphenyl ether tetracarboxylic dianhydride (ODPA) to obtain a high-purity polyimide precursor resin solid (PAE-1-5: BODA / ODPA-44ODA).

[0066] Resin Synthesis Example 6

[0067] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by a mixture of 24.31 g (0.05 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) and 16.11 g (0.05 mol.) 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA) to obtain a high-purity polyimide precursor resin solid (PAE-1-6: BODA / BTDA-44ODA).

[0068] Resin Synthesis Example 7

[0069] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 24.31 g (0.05 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) and 14.71 g (0.05 mol.) 3,3,4',4'-biphenyltetracarboxylic dianhydride (abbreviated as: BPDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-7: BODA / BPDA-44ODA).

[0070] Resin Synthesis Example 8

[0071] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 24.31 g (0.05 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) and 22.21 g (0.05 mol.) 2,2-bis(4-benzenetetracarboxylic anhydride)hexafluoropropane (abbreviated as: 6FDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-8: BODA / 6FDA-44ODA).

[0072] Resin Synthesis Example 9

[0073] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 24.31 g (0.05 mol.) 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride (BODA, Mw = 486.32, 166-167 °C) and 10.09 g (0.05 mol.) pyromellitic anhydride (abbreviated as PMDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as PAE-1-9: BODA / PMDA-44ODA).

[0074] Resin Synthesis Example 10

[0075] In resin synthesis example 5, 20.02 g (0.1 mol.) 4,4'-diaminodiphenyl ether (44ODA) was replaced by 20.02 g (0.1 mol.) 3,4'-diaminodiphenyl ether (34ODA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-10: BODA / ODPA-34ODA).

[0076] Resin Synthesis Example 11

[0077] In resin synthesis example 5, 20.02 g (0.1 mol.) of 4,4'-diaminodiphenyl ether (44ODA) was replaced by 29.22 g (0.1 mol.) of 1,4-bis(3-aminophenoxy)-benzene (abbreviated as 134APB) to obtain a high-purity polyimide precursor resin solid (abbreviated as PAE-1-11: BODA / ODPA-134APB).

[0078] Resin Synthesis Example 12

[0079] In resin synthesis example 5, 20.02 g (0.1 mol.) of 4,4'-diaminodiphenyl ether (44ODA) was replaced by 29.22 g (0.1 mol.) of 1,4-bis(4-aminophenoxy)-benzene (abbreviated as 144APB) to obtain a high-purity polyimide precursor resin solid (abbreviated as PAE-1-12: BODA / ODPA-144APB).

[0080] Resin Synthesis Example 13

[0081] In resin synthesis example 5, 20.02 g (0.1 mol.) 4,4'-diaminodiphenyl ether (44ODA) was replaced by 41.03 g (0.1 mol.) 2,2-bis[4-(4-aminophenoxy)phenyl)]propane (abbreviated as BAPP) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-13: BODA / ODPA-BAPP).

[0082] Resin Synthesis Example 14

[0083] In resin synthesis example 5, 20.02 g (0.1 mol.) of 4,4'-diaminodiphenyl ether (44ODA) was replaced by 42.82 g (0.1 mol.) of 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (abbreviated as: 6FAPB) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-14: BODA / ODPA-6FAPB).

[0084] Resin Synthesis Example 15

[0085] In resin synthesis example 5, 20.02 g (0.1 mol.) of 4,4'-diaminodiphenyl ether (44ODA) was replaced by 50.43 g (0.1 mol.) of 1,4-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (abbreviated as: 6FBAB) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-1-15: BODA / ODPA-6FBAB).

[0086] Comparative Synthetic Resins 1-4

[0087] Comparative Synthetic Resin 1

[0088] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 30.06 g (0.10 mol.) 3,3,4',4'-diphenyl ether tetracarboxylic dianhydride (abbreviated as: ODPA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-2-1: ODPA-44ODA).

[0089] Comparative Synthetic Resin 2

[0090] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by 29.42 g (0.10 mol.) 3,3,4',4'-biphenyltetracarboxylic dianhydride (abbreviated as: BPDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-2-2: BPDA-44ODA).

[0091] Comparative Synthetic Resin 3

[0092] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by a mixture of 15.03 g (0.05 mol.) 3,3,4',4'-diphenyl ether tetracarboxylic dianhydride (abbreviated as: ODPA) and 14.71 g (0.05 mol.) 3,3,4',4'-biphenyl tetracarboxylic dianhydride (abbreviated as: BPDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-2-3: ODPA / BPDA-44ODA).

[0093] Comparative Synthetic Resin 4

[0094] In resin synthesis example 1, 33.22 g (0.10 mol.) 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride (2,2-Bis(BCDA, Mw = 332.21, 187-188 °C) was replaced by a mixture of 16.11 g (0.05 mol.) 3,3',4,4'-benzophenone tetracarboxylic dianhydride (abbreviated as: BTDA) and 14.71 g (0.05 mol.) 3,3,4',4'-biphenyltetracarboxylic dianhydride (abbreviated as: BPDA) to obtain a high-purity polyimide precursor resin solid (abbreviated as: PAE-2-4:BTDA / BPDA-44ODA).

[0095] Negative photosensitive PSPI resin liquid

[0096] Examples 1-5 and Comparative Examples 1-2

[0097] Example 1

[0098] In a cleanroom equipped with a yellow light, 100g of the polyimide precursor resin PAE-1-1 prepared in Example 1 of the present invention was weighed and dissolved in a mixed solvent (B) of 80g NMP and 20g ethyl lactate (EL) to form a homogeneous solution. Then, the following components were added sequentially: photocurable monomer (C): 8g ethylene glycol diethyl ether methacrylate (4EM), photocurable initiator (D-1): 1.0g 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl) oxime, and other components (E). The other components (E) included 0.25g diarylsulfonium salt (E-1), 2.5g 2,6-dimethoxymethyl-4-tert-butylphenol (E-2), 0.5g bis(triethanolamine)diisopropoxide titanium (E-3), 0.5g 5-methyl-1H-benzotriazole (E-4), and 0.5g... N-Phenylacetyldiethanolamine (E-5), 0.5 g of γ-glycidyl etheroxypropyltrimethoxysilane (E-6), and 0.5 g of N-nitrosodiphenylamine (E-7) were stirred at room temperature for 1 h to obtain a negative PSPI resin composition solution. The prepared negative PSPI resin solution had a solids content of 35 wt.% and a solution viscosity of 3500 mPa·s.

[0099] The aforementioned negative PSPI resin solution is uniformly coated onto the surface of a 12-inch silicon wafer or a large-area glass substrate using a spin coating process. After baking at 100-110 °C for 1-3 min, a mask is placed on the surface and exposed using ultraviolet lamps (i and g lines). The substrate is then developed by spraying with cyclopentanone developer, rinsed with propylene glycol methyl ether acetate, and cured in a nitrogen-protected oven (170 °C / 1 h, 230 °C / 1 h) to obtain a stereolithographic pattern formed by curing the polyimide film.

[0100] The performance of the prepared negative PSPI resin solution was evaluated using the above evaluation method. The evaluation results are as follows: ① Photolithography processability: pattern steepness is 0.85, photolithography resolution is 4.5μm, rated as "excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength is 100MPa, elongation at break is 56%, rated as "excellent"; ③ Copper adhesion: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ④ Chemical corrosion resistance: film thickness change rate is 0.65%, no microcracks or defects were observed, rated as "excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑥ Residual internal stress: 25 MPa, rated as "excellent"; ⑦ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".

[0101] Example 2

[0102] In Example 1, PAE-1-1 was replaced with PAE-1-2, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.87, photolithography resolution was 4.6 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 110 MPa, elongation at break was 46%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.68%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0103] Example 3

[0104] In Example 1, PAE-1-1 was replaced with PAE-1-3, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.88, photolithography resolution was 4.4 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 117 MPa, elongation at break was 66%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.65%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 24 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0105] Example 4

[0106] In Example 1, PAE-1-1 was replaced with PAE-1-4, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.90, photolithography resolution was 4.2 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 110 MPa, elongation at break was 58%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.56%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 22 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0107] Comparative Example 1

[0108] PAE-1 in Example 1 was replaced by PAE-2-1 in Comparative Synthesis Example 1, with all other aspects remaining the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.84, photolithography resolution was 6.8 μm, rated as "Good"; ② Comprehensive mechanical properties of the thin film: tensile strength was 110 MPa, elongation at break was 55%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.63%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 34 MPa, rated as "Good"; ⑦ Comprehensive performance evaluation: two indicators were "Good", rated as "Good".

[0109] Comparative Example 2

[0110] PAE-1-1 in Example 1 was replaced by PAE-2-2 in Comparative Synthesis Example 2, with all other aspects remaining the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.84, photolithography resolution was 10.4 μm, rated as "poor"; ② Comprehensive mechanical properties of the thin film: tensile strength was 117 MPa, elongation at break was 55%, rated as "excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.76%, no microcracks or defects were observed, rated as "excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑥ Residual internal stress: 35 MPa, rated as "poor"; ⑦ Comprehensive performance evaluation: two indicators were "poor", rated as "poor".

[0111] Table 1 Comparison of results between Examples 1-4 and Comparative Examples 1-2

[0112] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 PAE-1 PAE-1-1BCDA-44ODA PAE-1-2BODA-44ODA PAE-1-3BDDA-44ODA PAE-1-4IPDA-44ODA PAE-2-1ODPA-44ODA PAE-2-2BPDA-44ODA Solid content of adhesive (wt.%) 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 <![CDATA[Adhesive viscosity, mPa.s (23 ℃ )]]> 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 <![CDATA[Curing temperature ( ℃ / h)]]> 230 / 1 230 / 1 230 / 1 230 / 1 230 / h 230 / h

[0113] Table 1 compares the effects of changes in the main chain structure of the PAE-1 series of photosensitive polyaminate resins (including PAE-1-1, 1-2, 1-3, and 1-4) in Examples 1 to 4 on the overall properties of the prepared negative photosensitive PSPI resins. The results show that the negative photosensitive PSPI resin solution formed by thoroughly mixing PAE-1-1 or PAE-1-2, PAE-1-3, and PAE-1-4 as photocrosslinking polyaminate resins with photocrosslinking agents, photosensitizers, thermal crosslinking agents, low-temperature curing accelerators, polymerization inhibitors, copper discoloration inhibitors, tackifiers, and toughening agents exhibits excellent overall properties. However, the negative photosensitive PSPI resin prepared by replacing BCDA and BODA with ODPA or BPDA was rated as "good" or "poor" in terms of photolithographic processability and residual internal stress.

[0114] Example 5

[0115] In Example 1, PAE-1-1 was replaced with PAE-1-5, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.88, photolithography resolution was 4.6 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 115 MPa, elongation at break was 52%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.67%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0116] Example 6

[0117] In Example 1, PAE-1-1 was replaced with PAE-1-6, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.87, photolithography resolution was 4.2 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 114 MPa, elongation at break was 47%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.65%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 25 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0118] Example 7

[0119] In Example 1, PAE-1-1 was replaced with PAE-1-7, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.90, photolithography resolution was 4.2 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 113 MPa, elongation at break was 64%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.68%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0120] Example 8

[0121] In Example 1, PAE-1-1 was replaced with PAE-1-8, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.91, photolithography resolution was 4.7 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 118 MPa, elongation at break was 56%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.57%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 24 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0122] Example 9

[0123] In Example 1, PAE-1-1 was replaced with PAE-1-9, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.89, photolithography resolution was 6.7 μm, rated as "Good"; ② Comprehensive mechanical properties of the thin film: tensile strength was 112 MPa, elongation at break was 59%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.56%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 28 MPa, rated as "Good"; ⑦ Comprehensive performance evaluation: two indicators were "Good", rated as "Good".

[0124] Comparative Example 3

[0125] In Example 1, PAE-1-1 was replaced by PAE-2-3 in the comparative synthetic resin 3, with all other aspects remaining the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.85, photolithography resolution was 8.8 μm, rated as "Good"; ② Comprehensive mechanical properties of the thin film: tensile strength was 117 MPa, elongation at break was 56%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.65%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 34 MPa, rated as "Good"; ⑦ Comprehensive performance evaluation: two indicators were "Good", rated as "Good".

[0126] Comparative Example 4

[0127] In Example 1, PAE-1-1 was replaced by PAE-2-4 in the comparative synthetic resin 4, with all other aspects remaining the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.85, photolithography resolution was 10.6 μm, rated as "poor"; ② Comprehensive mechanical properties of the thin film: tensile strength was 116 MPa, elongation at break was 54%, rated as "excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.73%, no microcracks or defects were observed, rated as "excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑥ Residual internal stress: 37 MPa, rated as "poor"; ⑦ Comprehensive performance evaluation: two indicators were "poor", rated as "poor".

[0128] Table 2 Comparison of results between Examples 5-9 and Comparative Examples 3-4

[0129] Example 5 Example 6 Example 7 Example 8 Example 9 Comparative Example 3 Comparative Example 4 PAE-1 PAE-1-5BODA / ODPA(1 / 1)-44ODA PAE-1-6BODA / BTDA(1 / 1)-44ODA PAE-1-7BODA / BPDA(1 / 1)-44ODA PAE-1-8BODA / 6FDA(1 / 1)-44ODA PAE-1-9BODA / PMDA(1 / 1)-44ODA PAE-2-3ODPA / BPDA(1)-44ODA PAE-2-4BTDA / BPDA(1 / 1)-44ODA Solid content of adhesive (wt.%) 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 Adhesive viscosity, mPa·s (23 ℃) 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 Curing temperature (°C / h) 230 / 1 230 / 1 230 / 1 230 / 1 230 / 1 230 / h 230 / h

[0130] Table 2 compares the effects of changes in the resin backbone structure caused by different monomer molecular structures in the aromatic dianhydride mixtures of the PAE-1 series of photosensitive polyaminate resins (PAE-1-5, 1-6, 1-7, 1-8, 1-9) from Examples 5 to 9 on the overall performance of the prepared negative photosensitive PSPI resins. The results show that the photosensitive PSPI resin solution prepared by thoroughly mixing PAE resin (PAE-1-5 or PAE-1-6, PAE-1-7, PAE-1-8) as the photocrosslinking polyaminate resin with photocrosslinking agent, photosensitizer, thermal crosslinking agent, low-temperature curing accelerator, polymerization inhibitor, copper discoloration inhibitor, tackifier, and toughening agent exhibits excellent overall performance. The photosensitive PSPI resin solution prepared using PAE-1-9 as the photocrosslinking polyaminate resin is rated as "good" overall performance. The negative photosensitive PSPI resin prepared by replacing BODA with ODPA or BTDA is rated as "poor" overall performance.

[0131] Example 10

[0132] In Example 1, PAE-1-1 was replaced with PAE-1-10, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.91, photolithography resolution was 4.2 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 125 MPa, elongation at break was 53%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.68%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 20 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0133] Example 11

[0134] In Example 1, PAE-1-1 was replaced with PAE-1-11, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.90, photolithography resolution was 4.4 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 124 MPa, elongation at break was 49%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.66%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0135] Example 12

[0136] In Example 1, PAE-1-1 was replaced with PAE-1-12, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.88, photolithography resolution was 4.8 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 124 MPa, elongation at break was 62%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.64%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 21 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0137] Example 13

[0138] In Example 1, PAE-1-1 was replaced with PAE-1-13, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.89, photolithography resolution was 4.3 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 128 MPa, elongation at break was 54%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.57%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 22 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0139] Example 14

[0140] In Example 1, PAE-1-1 was replaced with PAE-1-14, while other aspects remained the same, to obtain a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated for performance using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.87, photolithography resolution was 4.5 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 128 MPa, elongation at break was 57%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.56%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0141] Example 15

[0142] In Example 1, PAE-1-1 was replaced with PAE-1-15, while other aspects remained the same, resulting in a negative PSPI resin solution. The prepared negative PSPI resin solution was evaluated using the aforementioned evaluation method. The evaluation results were as follows: ① Photolithography processability: pattern steepness was 0.85, photolithography resolution was 4.2 μm, rated as "Excellent"; ② Comprehensive mechanical properties of the thin film: tensile strength was 124 MPa, elongation at break was 58%, rated as "Excellent"; ③ Copper adhesion: cross-cut adhesion test result was 0 / 100, rated as "Excellent"; ④ Chemical corrosion resistance: film thickness change rate was 0.59%, no microcracks or defects were observed, rated as "Excellent"; ⑤ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑥ Residual internal stress: 23 MPa, rated as "Excellent"; ⑦ Comprehensive performance evaluation: all indicators were excellent, rated as "Excellent".

[0143] Table 3 Comparison of results from Examples 10-15

[0144] Example 10 Example 11 Example 12 Example 13 Example 14 Example 15 PAE-1 PAE-1-10BODA / ODPA(1 / 1)-34ODA PAE-1-11BODA / ODPA(1 / 1)-134APB PAE-1-12BODA / ODPA(1 / 1)-144APB PAE-1-13BODA / ODPA(1 / 1)-BAPP PAE-1-14BODA / ODPA(1 / 1)-6FAPB PAE-1-15BODA / ODPA(1 / 1)-6FBAB Solid content of adhesive (wt.%) 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 35±2.0 Adhesive viscosity, mPa·s (23 ℃) 3500±100 3500±100 3500±100 3500±100 3500±100 3500±100 Curing temperature (°C / h) 230 / 1 230 / 1 230 / 1 230 / 1 230 / 1 230 / 1

[0145] Table 3 compares the effects of changes in the resin backbone structure caused by the different monomer molecular structures of the aromatic dianhydride mixture in the PAE-1 series of photosensitive polyaminate resins (PAE-1-10, 1-11, 1-12, 1-13, 1-14, 1-15) from Examples 10 to 15 on the overall performance of the prepared negatively photosensitive PSPI resins. The results show that the photosensitive PSPI resin solutions formed by thoroughly mixing PAE resins (PAE-1-10, 1-11, 1-12, 1-13, 1-14, 1-15) as photocrosslinking polyaminate resins with photocrosslinking agents, photosensitizers, thermal crosslinking agents, low-temperature curing accelerators, polymerization inhibitors, copper discoloration inhibitors, tackifiers, and toughening agents all received an "excellent" overall performance evaluation.

[0146] The results above show that the photosensitive PSPI resin liquid, formed by thoroughly mixing photosensitive polyaminate resin, photocrosslinking agent, photosensitizer, thermal crosslinking agent, low-temperature curing accelerator, polymerization inhibitor, copper discoloration inhibitor, adhesion promoter, and toughening agent, has excellent photolithography processability. It can form a uniformly thick liquid film on a large-area glass substrate surface by spin coating on the silicon wafer surface or by film formation processes such as inkjet printing and curtain coating. After pre-baking, exposure, development, rinsing, and heat curing (170-230 ℃), the liquid film can form a high-quality three-dimensional photolithography pattern with high aperture resolution. The cured resin of the above-mentioned photolithography pattern has excellent comprehensive mechanical properties, resistance to damp heat, resistance to chemical corrosion, and copper surface adhesion. Meanwhile, the multilayer metal interconnect (RDLs) structure made of the negative PSPI resin solution has low internal stress, which can significantly reduce the warpage of the reconstructed wafer and avoid interlayer cracking of the RDLs structure. It is suitable for fabricating multilayer metal interconnect (RDLs) on the surface of silicon wafers and large-area glass substrates.

Claims

1. A high-resolution negative photosensitive polyimide resin adhesive, comprising: The composition includes 100 parts of photocrosslinkable polyamide ester resin, 50-150 parts of solvent, 0.01-20 parts of photocurable crosslinking agent, 0.01-10 parts of photocurable initiator, 0.01-10 parts of photosensitizing accelerator, 0.01-10 parts of thermal crosslinking agent, 0.01-10 parts of low-temperature curing accelerator, 0.01-10 parts of polymerization inhibitor, 0.01-10 parts of copper discoloration inhibitor, 0.01-10 parts of tackifier, and 0.01-10 parts of toughening agent; wherein: The main chain structure of the photocrosslinkable polyamic acid ester resin contains highly transparent aliphatic segments and methacrylate groups that can undergo photocrosslinking reactions after being irradiated with ultraviolet light.

2. The negative photosensitive polyimide resin liquid according to claim 1, wherein: The photocrosslinked polyaminate resin is prepared by the following method: (1) Aromatic tetracarboxylic dianhydride and hydroxyl-containing (meth)acrylate are dissolved in an organic solvent and esterified under heating to form an aromatic diester dianhydride solution; (2) The aromatic diester diacid solution is reacted with thionyl chloride to form the corresponding aromatic diester diacyl chloride solution; (3) Under cooling conditions, the aromatic diamine solid is added in portions to the above aromatic diester diacyl chloride solution and stirred at room temperature to 40°C for 0.1 to 10 h; then, a reactive end-capping agent is added and the reaction is continued to be stirred to form a photocrosslinked polyamic acid ester resin solution.

3. The negative photosensitive polyimide resin liquid according to claim 2, wherein: The aromatic tetracarboxylic dianhydride includes two types: aromatic tetracarboxylic dianhydride-1 and aromatic tetracarboxylic dianhydride-2. Aromatic tetracarboxylic dianhydride-1 includes at least one of 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyloctane dianhydride, 2,7-bis(3,4-dicarboxyphenyl)-2,7-dimethyldodecane dianhydride, and bis(triphenylamine)-bisphenol A ester. Aromatic tetracarboxylic dianhydride-2 includes at least one of pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, and 2,2-bis(4-benzenetetracarboxylic anhydride)hexafluoropropane, and a mixture thereof in any proportion. The weight ratio of aromatic tetracarboxylic dianhydride-1 to aromatic tetracarboxylic dianhydride-2 is 1~100:

100.

4. The negative photosensitive polyimide resin liquid according to claim 2, wherein: The hydroxyl (meth)acrylate includes at least one of 2-methacryloyloxyethanol, 2-hydroxy-3-methoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, and 2-acryloyloxyethanol, and a mixture thereof in any proportion. The organic solvent is selected from at least one of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, and tetrahydrofuran; The aromatic diamine includes at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)-benzene, and 2,2-bis[4-(4-aminophenoxy)phenyl)]propane; The reactive capping agent includes at least one of phthalic anhydride, 3-methylphthalic anhydride, acetic anhydride, aniline, and methylamine.

5. The negative photosensitive polyimide resin liquid according to claim 1, wherein: The photocurable crosslinking agent includes at least one of diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and propylene glycol dimethacrylate, and the mass ratio of the agent to the photocrosslinkable polyamic acid ester resin is 0.1~10:100; The photocuring initiator includes at least one of benzophenone, 1-hydroxycyclohexylphenyl ketone, 2-methylthioxanone, and benzoyldimethyl ketal; The photosensitizer includes at least one of 4-morpholinobenzophenone and 4,4'-bis(diethylamino)benzophenone; the thermal crosslinking agent includes at least one of 2,6-dimethoxymethyl-4-tert-butylphenol and 2,6-dimethoxymethyl-p-cresol. The low-temperature curing accelerator includes at least one of bis(triethanolamine) diisopropoxide titanium and tetra(n-butanol) titanium; The polymerization inhibitor includes at least one of hydroquinone, N-nitrosodiphenylamine, and p-tert-butylcatechol; the copper color-changing inhibitor includes at least one of toluenetriazole, 5-methyl-1H-benzotriazole, and 2,6-di-tert-butyl-4-methylphenol. The adhesive aid includes at least one of γ-aminopropyltrimethoxysilane, γ-glycidyl etheroxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane; The toughening agent refers to a thermoplastic polymer resin containing reactive functional groups with a weight average molecular weight of less than 100,000, including at least one of thermoplastic polyimide resin, silicone-modified polyimide resin, and polymethacrylate resin.

6. A method for preparing a negatively photosensitive polyimide resin liquid according to any one of claims 1 to 5, comprising: (1) Aromatic tetracarboxylic dianhydride and hydroxyl-containing (meth)acrylate are dissolved in an organic solvent and esterified under heating to form an aromatic diester dianhydride solution; (2) The aromatic diester diacid solution is reacted with thionyl chloride to form an aromatic diester diacid chloride solution; (3) Under cooling conditions, the solid aromatic diamine is added in portions to the solution of aromatic diester diacyl chloride, and the mixture is stirred at room temperature to 40°C for 0.1 to 10 hours. A reactive end-capping agent is added to continue the reaction to form a photocrosslinked polyamic acid ester resin solution. (4) Mix the photocrosslinked polyamic acid ester resin with the solvent, and stir and dissolve it under yellow light and nitrogen protection to form a homogeneous solution; (5) Add photocurable crosslinking agent, photocurable initiator, photosensitive accelerator, thermal crosslinking agent, low temperature curing accelerator, polymerization inhibitor, copper discoloration inhibitor, adhesion promoter and toughening agent to the homogeneous solution in step (4), and stir until completely dissolved to form a homogeneous solution; (6) Adjust the solid content and viscosity of the homogeneous solution obtained in step (5), filter, and obtain negative PSPI resin solution.

7. The preparation method according to claim 6, wherein: In step (1), the molar ratio of aromatic tetracarboxylic dianhydride to hydroxyl (meth)acrylate is 1:1.5~2.0, the esterification reaction temperature is 20~150℃, and the reaction time is 0.5~96h; The molar ratio of the aromatic diester diacid to thionyl chloride in step (2) is 1:1.5~3, the reaction temperature is -30~50℃, and the reaction time is 1~48h; In step (3), the molar ratio of aromatic diester diacyl chloride to aromatic diamine is 1:0.8~1.2, the reaction temperature is -30~10℃, and the reaction time is 0.5~96h.

8. The preparation method according to claim 6, wherein: When the solid content of the negative PSPI resin solution in step (6) is 10-45 wt.%, the solution viscosity at room temperature is 100-5500 mPa·s, and the solution viscosity change rate is less than 10% after being placed at room temperature for 7 days.

9. A negative PSPI resin solution prepared by any one of the preparation methods according to claims 6 to 8.

10. The application of a negative PSPI resin adhesive according to any one of claims 1 to 5 or 9 in the preparation of a multilayer interlayer insulating layer and passivation protective layer on the surface of silicon wafers and large-area glass substrates.